The unexpected identification of the cannabimimetic, 5F-ADB, and dextromethorphan in commercially available cannabidiol e-liquids. (January 2019) - Poklis, Justin L.; Mulder, Haley A.; Peace, Michelle R.
Graphical abstract: Highlights: Analysis of unregulated cannabidiol e-liquids potentially used for medical or health reasons. Four CBD only e-liquids determined to contain 5F-ADB or dextromethorphan. Illustrates the potential quality control issues that occur in an unregulated industry. Abstract: Electronic cigarettes (e-cigarettes) were developed as an alternative method for nicotine delivery and had a significant surge in popularity. E-liquids are formulations used in e-cigarettes, and consist of a ratio of propylene glycol (PG) and vegetable glycerin (VG), a pharmaceutical and/or herbal remedy and, usually, a flavoring agent. Presented is the evaluation of nine cannabidiol (CBD) e-liquids from a single manufacturer for cannabinoids and other psychoactive compounds by Direct Analysis in Real Time Mass Spectrometry (DART-MS) and Gas Chromatography Mass Spectrometry (GC/MS). The analysis of these products resulted in the detection of CBD in all nine produces and the unexpected detections of 5-fluoro MDMB-PINACA (5F-ADB) in four of the products and dextromethorphan (DXM) in one of the products. The analysis of these products illustrates the potential quality control issues that can occur in an unregulated industry. CBD products are believed by many users to offer heath benefits, but the detection of a dangerous cannabimimetic, 5F-ADB, and DXM in these products illustrates the need for oversight.